PENERAPAN MEDIA KARTU MAJAS TERINTEGRASI DENGAN KUIS JEOPARDY MELALUI MODEL KOOPERATIF TEAM GAMES TOURNAMENT UNTUK MENINGKATKAN HASIL BELAJAR MATERI MAJAS SISWA KELAS V SD ISLAM WALISONGO BRONDONG - Halimatus Sakdiyah, Halimatus; Saeful Mizan; Badri Atul Fikriyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve the learning outcomes of fifth-grade students at SD Islam Walisongo Brondong in the subject of types of figurative language, namely metaphor, personification, and hyperbole. The main problem faced is the low level of student engagement during the learning process, which has an impact on low learning outcomes. Out of 22 students, only 6 were able to achieve the Learning Objective Achievement Criteria (LOAC) with a minimum score of 75. This study employed a Classroom Action Research (CAR) approach conducted in two cycles through the stages of planning, implementation, observation, and reflection. The research subjects consisted of 22 students, with a composition of 8 female students and 14 male students. The data collection techniques used included tests and observations. The results of the study showed a significant increase in learning outcomes and learning activities. Student learning completeness increased from 59.09% in cycle I to 81.82% in cycle II. Teacher activity, which was initially categorized as “good” with a percentage of 71.87%, increased to 93.75% and was categorized as “very good.” Similarly, student activity increased from 72.40% to 88.96%. These findings demonstrate that the application of metaphor cards combined with Jeopardy quizzes in the Teams Games Tournament (TGT) cooperative learning model can enhance students' understanding of the material and encourage their active participation in Indonesian language learning.